Electrochemical and Spectroscopic Studies on Triarylamine‐Polychlorotriphenylmethyl Dyads with Particularly Strong Triarylamine Donors. Issue 33 (1st September 2021) - Breimaier, Stefanie; Winter, Rainer F.
Abstract: We present two new donor‐acceptor dyads composed of a polychlorotriphenylmethyl radical (PTM . ) as the acceptor (A) and bis(4‐dimethylaminophenyl)(phenyl)amine (TPAN ) or 2, 2':6', 2'':6'', 6‐trioxytriphenylamine (TOTA ) as particularly electron‐rich triarylamine (TAA ) donors (D). We assessed their electrochemical properties and electronic structures by cyclic voltammetry, UV/vis/NIR spectroscopy, EPR spectroscopy and quantum chemical calculations. By establishing the spectroscopic fingerprints of the oxidized and reduced forms, we probe for the possible coexistence of a zwitterionic TAA + ‐PTM − valence tautomer (VT), besides neutral TAA‐PTM . . UV/vis/NIR and EPR spectroscopic studies at variable temperature and in various solvents however provide no indication for such equilibria. Quantitative spin counting experiments by EPR spectroscopy and quantum chemical calculations indicate that the one‐electron oxidized forms of these dyads possess an open‐shell singlet ground state which is energetically slightly below the triplet state Abstract : Two new donor‐acceptor dyads with a particular electron‐rich triarylamine (TAA) donor and the perchlorotriphenylmethyl radical acceptor (PCT) are probed for their propensity to equilibrate with their zwitterionic valence tautomers TAA + ‐PCT − . The UV/vis/NIR and EPR spectroscopic profiles of their oxidized and reduced forms were recorded, but failed to identify such isomers in the neutral state. The cations have an open‐shell singlet ground state, situated slightly below the triplet state.